Evaluation of the Omron MX3 Plus monitor for blood pressure measurement in adolescents - Destro Christofaro, Diego Giulliano; Casonatto, Juliano; Polito, Marcos Doederlein; Cardoso, Jefferson Rosa; Fernandes, Romulo [UNESP]; Guariglia, Debora Alves; Gerage, Aline Mendes; de Oliveira, Arli Ramos (Springer, 2009)
This study analyzed the accuracy/agreement of the Omron MX3 monitor on 165 adolescents. Blood pressure was measured by the automatic monitor connected in Y with the mercury column (three consecutive and simultaneous measures). The independent measures were analyzed, and the mean differences between systolic and diastolic measures for both methods were calculated and compared with British Hypertension Society (BHS) and Association for the Advancement of Medical Instrumentation (AAMI) criteria. The automatic monitor received the highest degree of BHS recommendations for systolic and diastolic blood pressures according to the BHS. The median (25th and 75th) difference between the observer and the monitor measurements was -2 (-6 and 1) mmHg for systolic and 0 (-3 and1) mmHg for diastolic pressures. The monitor also satisfies the AAMI standard for the studied population. In conclusion, the Omron MX3 Plus monitor can be considered reliable and valid for clinical practice and is in accordance with BHS and AAMI criteria.
Keywords: Blood pressure; Validation; Adolescents